Exploring the Role of Rural Tourism in Achieving Sustainable Rural Development - Pokharel, Suman; Bhattarai, Rudra Prasad (KMC Research Journal, 2022)
This study investigates the role of rural tourism in facilitating sustainable rural development, with a specific focus on Ghandruk region situated in Kaski district of Nepal. Employing a case study methodology, the researchers collected data through in-depth interviews conducted with a diverse range of stakeholders, including homestay owners, hotel owners, foreign tourists, local leaders, NGOs, government representatives, and farmers. The study findings highlight the positive impact of rural tourism activities on the social, economic, and environmental dimensions of development within the study region. The research sheds light on the potential of rural tourism in improving the standard of living for rural residents while also preserving local culture and resources. The findings contribute to the existing literature on rural tourism and offer insights for policymakers and stakeholders in leveraging rural tourism as a catalyst for sustainable rural development.